(untitled) (International Journal of Food and Nutritional Sciences, 2022)
E-banking, also known as electronic banking, is another paradigm shifter that has revolutionized the traditional banking system. E-banking is the electronic delivery of banking services and transactions through various digital channels such as the Internet, mobile apps and ATMs